CASTOR BEAN (RICINUS COMMUNIS L.) CROP AND ITS CURRENT SITUATION IN ECUADOR - Orlando-López, José Francisco (2022)
The castor (Ricinus communis L.) belongs to the Euphorbiaceae family, which is established on all continents. It generates great interest worldwide thanks to the content of oil extracted from the seed, which can be used in the production of biofuels, pharmaceutical and cosmetic products, organic fertilizers, among other uses. The main of this work is to analyze the current situation of the cultivation of castor in Ecuador. The literature review was carried out, carrying out an exhaustive search in the Google Scholar, Scielo, Web of Science, and Scopus databases, from 1973 to 2022, with a total of 52 scientific manuscripts. Currently, the supply of seeds for extraction companies has been affected in Ecuador and has put the companies adrift, because there are few producers that produce it, and it is not a technified crop or with incentives from the Ecuadorian government. It is expected that with the launch of the castor variety INIAP – 402 “LA ROJA”, farmers are motivated to sow and that there are more attractive prices from businessmen and thus favor the producer. Keywords: biofertilizer – castor – Euphorbiaceae – economic importance – oil